2018
DOI: 10.1371/journal.pntd.0006945
|View full text |Cite|
|
Sign up to set email alerts
|

Asymptomatic carriage of Streptococcus pneumoniae detected by qPCR on the palm of hands of populations in rural Senegal

Abstract: Aside from malaria, infectious diseases are an important cause of death in sub-Saharan Africa and continue to pose major public health problems in African countries, notably pneumonia. Streptococcus pneumoniae remains the most common bacterial cause of pneumonia in all age groups. The skin is one of the main infection sites followed by the oropharynx. The skin carriage of certain pathogenic bacteria such as S. pneumoniae is often ignored or under-diagnosed. Finally, the mode of transmission of these infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A study of CL-K1 knockout mice showed that a lack of CL-K1 leads to susceptibility to S. pneumoniae infection ( 90 ). S. pneumoniae has been isolated as a major pathogen carried by the skin ( 91 ). Therefore, CL-K1 possibly participates in the defense against pathogens in the skin.…”
Section: Role Of Collectins In Skin Immune Homeostasismentioning
confidence: 99%
“…A study of CL-K1 knockout mice showed that a lack of CL-K1 leads to susceptibility to S. pneumoniae infection ( 90 ). S. pneumoniae has been isolated as a major pathogen carried by the skin ( 91 ). Therefore, CL-K1 possibly participates in the defense against pathogens in the skin.…”
Section: Role Of Collectins In Skin Immune Homeostasismentioning
confidence: 99%
“…The positive control consisted of a suspension made from the swabbing of a healthy person, to which bacterial cultures were added. The strains used as positive controls are available on the Rickettsia Unit Strains Collection (CSUR, WDCM 875) under the following accession numbers: S. pneumoniae CSURP5700, S. aureus CSURP2200 and S. pyogenes CSURP6897 (Ndiaye et al, 2018). For each species, approximately ten colonies were suspended in 200 mL PBS, and DNA was extracted (Ndiaye et al, 2018).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The primers and probes used for pathogenic identification are listed in Table 1. The quality of the DNA handling and the extraction of the swab suspensions was verified by quantitative PCR for a housekeeping gene coding for βactin, as previously described (Ndiaye et al, 2018;Mediannikov et al, 2010). Samples were considered to be positive if both specific qPCR reactions were positive using a cycle number at the threshold level for a log-based fluorescence (Ct) value <35.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Asymptomatic carriage is high in children (over 30%), especially in those under five years of age that plays a key role in the transmission of pneumococci to the majority of the human population [6]. Predisposing factors for asymptomatic carriage are attendance at kindergarten or school, number of children in the family, household crowding and low hygiene [7].…”
Section: Introductionmentioning
confidence: 99%